Training in open access for doctoral students: results of a survey of current and recent students and supervisors - Simon Wakeling; Monique Shephard; Hamid H. R. Jamali (Information Research: An International Electronic Journal)
Introduction. This study aimed to understand the extent to which doctoral students receive training relating to open access publishing, and the form of that training.